Preparation and thermal properties of heterogeneous composite phase change materials based on camphene-palmitic acid - Genc, Zuhal Karagoz; Canbay, Canan Aksu; Acar, Sureyya Seyma; Sekerci, Memet; Genc, Murat (Springer, 2015)
This study focuses on the preparation of camphene/palmitic acid mixture as novel phase change material for the first step of composite-based phase change materials. Camphene-palmitic acid-based composite phase change materials (PCMs) for thermal energy storage were prepared by vacuum impregnation method. The maximum incorporation percentage for camphene-palmitic into pyroclastic, fly ash, barite and marble powder were found to be 33.09, 55.5, 31.5 and 35.96 %, respectively. The differential scanning calorimetry analysis revealed that the composite PCMs were suitable applicants for building applications in terms of their appropriate phase change temperatures and extensive latent heat values. The SEM results showed that the homogeneity of the samples is good, and according to supporting materials porosity formation is observed. Thermal cycling test indicated that the form-stable composite PCMs have good thermal reliability and chemical stability although they were subjected to 2,000 melting/freezing cycling.
Keywords: Form-stable composite PCM; Camphene; Palmitic acid; Thermal energy storage